Enantioselective Construction of Bicyclic Pyran and Hydrindane Scaffolds via Intramolecular Rauhut–Currier Reactions Catalyzed by Thiourea-Phosphines - Li, Kaizhi; Jin, Zhichao; Chan, Wai-Lun; Lu, Yixin (ACS catalysis, 2018)
Highly enantioselective intramolecular RC reactions via desymmetrization of cyclohexadienones have been developed. By employing cyclohexadienones with a flexible ether or alkyl group linked internal enone moiety, optically enriched bicyclic pyran and hydrindane skeletons were constructed. Bifunctional phosphine catalysts bearing a thiourea moiety were found to effectively promote the reaction, and preliminary studies suggest that the hydrogen-bonding interaction between thiourea and carbonyl group is crucial and facilitates the otherwise flexible backbones to undergo the desired cyclization.